2005
DOI: 10.1038/sj.onc.1208508
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of extracellular signal-regulated kinases and HSP90 sensitizes human colon carcinoma cells to ionizing radiation

Abstract: Indomethacin, a common nonsteroidal anti-inflammatory drug, has been shown to enhance radiation-mediated cellkilling effect through the activation of p38 mitogenactivated protein kinase (MAPK). We found that indomethacin strongly reduced the basal level of extracellular signal-regulated kinases 1 and 2 (ERK1/2) in HT-29 human colon carcinoma cells. The inhibition of ERK1/2 by indomethacin was only observed in cells with high basal activities of ERK1/2 such as HT-29 cells, but not in cells with low basal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…4A and 5A). These results were in agreement with previous findings that combined the inhibition of signalregulated kinases and HSP90-sensitized colon carcinoma cells to ionizing radiation (25). HSP90 has also been reported to modulate Akt kinase activity (26) and to compromise the DNA damage in response to radiation (27).…”
Section: Discussionsupporting
confidence: 83%
“…4A and 5A). These results were in agreement with previous findings that combined the inhibition of signalregulated kinases and HSP90-sensitized colon carcinoma cells to ionizing radiation (25). HSP90 has also been reported to modulate Akt kinase activity (26) and to compromise the DNA damage in response to radiation (27).…”
Section: Discussionsupporting
confidence: 83%
“…Kobayashi et al 8) have reported that indomethacin reduced the basal level of ERK1/2 in human cells. We examined the possibility that indomethacin-induced strobilation could have resulted from the suppression of ERK activity by testing PD98059 and U0126, both inhibitors of the ERK signaling pathway, for their strobilation-inducing activity.…”
mentioning
confidence: 99%
“…The second effect was cellular growth inhibition by arresting cells at the S phase as like indomethacin. 29,30) Moreover, the effective concentrations of MW-03 used in the present study were at least 10-fold lower than that of indomethacin. Further experiments are needed in order to elucidate, for example, whether MW-03 exerts the same effects as NSAIDs.…”
Section: Resultsmentioning
confidence: 99%
“…30) Therefore, in an attempt to identify alternate/additional targets of MW-03 in LS174T cells, a cell-cycle analysis were performed with MW-03-treated LS174T cells using a flow cytometer. As shown in Fig.…”
Section: Effects Of Mw-03 On Pge 2 -Induced Camp Formationmentioning
confidence: 99%